Improving interagency collaboration, innovation and learning in criminal justice systems: supporting offender rehabilitation - Hean, Sarah (Springer eBook Collection, 2021)
1. Setting The Scene And Introduction, Sarah Hean, Berit Johnsen, Anu Kajamaa And Laure Kloetzer -- 2. Interorganisational Collaboration In A Norwegian Prison – Challenges And Opportunities Arising From Interagency Meetings, Päivikki Lahtinen, Anu Kajamaa, Laura Seppänen, Berit Johnsen, Sarah Hean, Terhi Esko -- 3. Mirrors Of Prison Life – From Compartmentalised Practice Towards Boundary Crossing Expertise, Søren Walther Nielsen And Anu Kajamaa -- 4. ‘Living With’ Interagency Collaboration – Three Sustaining Practices, Tine Murphy, Marie Kirstejn Aakjaer, Eva Pallesen, Charlotte Rosenberg -- 5. The Application Of Norwegian Humane Ideals By Front- Line Workers When Collaboratively Reintegrating Inmates Back Into Society, William Dugdale And Sarah Hean -- 6. Tracing The Historical Development Of A Service Model For Interagency Collaboration: Contradictions As Barriers And Potential Drivers For Change, Paulo Rocha And Sarah Hean -- 7. Mentoring In Practice. Rebuilding Dialogue With Mentees’ Stories, Laure Kloetzer, Jo Wells, Laura Seppänen And Sarah Hean -- 8. A Colab Model Of Workplace Transformation In The Criminal Justice Context, Sarah Hean ,Marie Aakjær, Laure Kloetzer, Laura Seppännen, Anu Kajamaa, Päivikki Lahtinen, Tine Murphy -- 9. Facilitation Of Developmental Tasks In Prisons: Applying The Method Of Human-Centred Co-Evaluation, Laura Seppänen, Heli Heikkilä, Anu Kajamaa, Päivikki Lahtinen, Hilkka Ylisassi -- 10. Interprofessional Collaboration Concerning Offenders In Transition Between Mental Health And Criminal Justice Services. Pincom Used As A Framework For Hcr-20v3 Assessment., Atle Ødegård And Stål Bjørkly -- 11. Early Recognition Method: ‘Opening Doors’ In Risk Management Dialogue Between Mental Health And Prison Services 254, Frans Fluttert, Gunnar Eidhammer, Karl Yngvar Dale.12- People In Contact With Criminal Justice Systems Participating In Service Redesign: Vulnerable Citizens Or Democratic Partners?, Jonathan Parker, Vanessa Heaslip, Sara Ashencaen Crabtree, Berit Johnsen And Sarah Hean -- 13. Avenues Of Opportunity: Journeys Of Activities Through Third Sector Organisations, Angela Turner-Wilson, Stuart Dearborn And Catherine Bullen -- 14. Facilitating Understanding Of Ex-Prison Service Users’ Needs: The Utility Of Q Method As A Means Of Representing Service User Voices In Service Development, Siv Elin Nord Sæbjørnsen, Atle Ødegård And Sarah Hean -- 15. Do We Need The Users’ Voice? An Empirical Research Example Comparing Views Of Service Providers And Ex-Prisoners. Implications For Practice, Siv Elin Nord Sæbjørnsen, Sarah Hean, Kristin Røvik, Bjørn Kjetil Larsen And Atle Ødegård -- 16. Reflecting On Researcher/Practice Relationships In Prison Research : A Contact Hypothesis Lens, Sarah Hean, Liv Jorunn Skippervik, Richard Heslop, Caroline Stevens -- 17. Developing A Training Programme For Collaborative Practices Between Criminal Justice And Mental Health Services: The Gap Between Intentions And Reality, Atle Ødegård And Elisabeth Willumsen. .